Adapting a consensus process for survivors of domestic abuse and child maltreatment: a brief report about adopting a trauma-informed approach in multistakeholder workshops - Ruth Gilbert; Gene Feder; Eszter Szilassy; Katherine Cowan; Emma Howarth; Karen Johns; Alison Gregory; Ursula Lindenberg; Claire Powell (BMJ Open)
Purpose Among health researchers, there is a growing appreciation of the importance of the involvement of service users and members of the public. This recognition has not only resulted in involvement guidelines and improved research ethics but also an increasing use of consensus processes with service users and members of the public to determine research priorities and questions and to agree outcomes to be measured in intervention studies. There is, however, limited advice about how to safely involve survivors of violence and abuse in consensus-based studies.Methods/results This commentary provides an overview of the adaptations made to a process of core outcome set development, to ensure that survivors of violence and abuse felt safe, heard and supported, and able to contribute in a meaningful way.Conclusions We advocate for an iterative process of listening to and learning from survivors, as well as buy-in from funders to ensure research studies are appropriately resourced and involve sufficient planning time.